Sensores em Fibra Óptica Baseados em Interferêmetros de Sagnac - Pizzaia, João Paulo Lebarck (2021)
The use of all-in-fiber optical sensors to monitor physical quantities has been gaining ground in the industry, especially for use in areas classified as potentially explosive. Among the devices used in this function we can highlight the interferometers that are the object of constant research due to their high accuracy for measurements in various fields such as temperature, pressure, displacement, magnetic fields, vibration, among others. This work presents, through numerical simulations and experimentation, setups for measurement systems using the in-fiber Sagnac interferometer model for flow and temperature sensing, in order to discuss the results and the theory behind the operational principle of them. The results found show sensitivities of 2.59×10−¹mW/ms−¹ for the proposed setup for flow measurement using the effect known as "Fresnel drag" for a pipeline measuring 10 cm of internal diameter, and up to -1.62 nm /◦C and 214pm/◦C for temperature sensors using, respectively, Polarization Maintaning Fiber (PMF) and Erbium Doped Fiber (EDF) segments as sensing elements. Such devices proved to be effective, due to their high sensitivities, resolution, linearity and operating range, therefore, they can be a viable option for laboratory and industrial use, especially for environments with the possibility of formation of an explosive atmosphere.